(untitled) (Vietnam Journal of Community Medicine, 2024)
Cerebral ischemia is a severe postoperative complication in surgeries using sitting position, especially in the shoulder arthroscopy. The sitting position, also known as the beach chair position, is increasingly used by surgeons because of its superiority in the surgical field and the reduction in the rate of brachial plexus injury induced traction. However, this position increases the incidence of hemodynamic complications, including cerebral infarction resulting from prolonged hypotension. We report a case of severe postoperative cerebral infarction, a 50-year-old male patient with historic well controlled hypertension and unconfirmed carotid arterial narrow, underwent arthroscopic shoulder surgery in the “beach chair position”. After stable induction of anesthesia and changing the position from supine to beach chair position, the patient’s blood pressure decreased. After 5 minutes of management with fluid resuscitation and the use of Ephedrine, the blood pressure gradually stabilized and returned to the patient’s post-induction baseline level. The surgery and subsequent anesthesia process were maintenanced relatively stable, with blood pressure oscillated at 10% lower than the patient’s baseline. After extubation in the recovery room, we found the patient to be agitated, showing signs of aphasia, right central cranial nerve VII palsy, and right hemiplegia. MRI pictures showed extensive left hemisphere cerebral infaction and terminal left internal carotid artery stenosis. The patient was transferred to a stroke center for treatment, where, after two weeks, his consciousness and motor function improved, but there was no complete recovery of neurological function.